Teacher Certification: A Way to Lead Teacher for Professional Development and Lifelong Learning - Kuzairi Kuzairi (STKIP PGRI Banjarmasin, 2019)
Indonesian Government launched teacher certification program in order to increase the quality of teachers. This policy is expected to foster teacher’s competences and prosperity. In terms of competency, this program enhances teachers to develop their professionalism especially in teaching and other academic activities. Test and training are provided to take this program. Several requirements such as the minimum qualification, teacher’s portfolio are also given as the elements or components of the teacher certification program administration. Dealing with the prosperity, teachers who passed this program are also given financial support. Some studies on the effectiveness of teacher certification program were conducted. The results showed that this program does not guarantee teachers to have quality improvement. However, it does not mean this program is not successful at all or it does not have any advantage or contribution for teachers. Therefore, this paper aims to discuss on how far teacher certification program lead teachers to develop their professionalism and bring them into lifelong learning activities or situation.